User Experience (UX) Analysis and Affective Responses of Early Childhood Learners toward the Literacy Features of the Sekolah Enuma Application - Annisa Wahyuni; Mukhlis Mukhlis; Imam Muthie; Riris Wahyuningsih; Mega Cahya Dwi Lestari (Journal of Childhood Development, 2026)
The rapid integration of digital technology in early childhood education highlights the need for learning media that are not only cognitively effective but also emotionally engaging. The Sekolah Enuma literacy application represents an innovative digital tool whose effectiveness should be examined from both User Experience (UX) and children’s affective responses. This study aims to analyze the quality of UX and the affective responses of young children when interacting with literacy features, as well as to explore the relationship between these aspects in supporting learning outcomes. This study employed a qualitative descriptive approach. Data were collected through participatory observation, semi-structured interviews with teachers and facilitators serving, and documentation. Data analysis followed the interactive model of data reduction, data display, and conclusion drawing. The findings indicate that the application demonstrates good UX quality, characterized by ease of use, intuitive navigation, and visually engaging design. Most children exhibited positive affective responses such as enjoyment and enthusiasm, although some experienced confusion when encountering more complex instructions. The results reveal a strong relationship between UX quality and affective responses, which significantly influences children’s learning engagement. In conclusion, well-designed UX contributes substantially to positive emotional experiences and enhances the effectiveness of early literacy learning. Future research is recommended to adopt mixed-method approaches and longitudinal designs to provide more comprehensive insights.